Behavior of buffalo heifers reared in shaded and unshaded pastures during the dry season on Marajó Island, Pará, Brazil - Almeida, Jean Caio Figueiredo de; Joset, Waléria Cristina Lopes; Noronha, Rafaela de Paula Pachêco; Barbosa, Antônio Vinicius Correa; Lourenço Júnior, José de Brito; Silva, Jamile Andréa Rodrigues da (Acta Scientiarum. Animal Sciences, 2019)
The objective of this research was to evaluate the behavior of twenty buffalo heifers reared during the dry season on Marajó Island, Pará, Brazil. The animals were distributed into two groups, those with shade (WS) and those without shade (WOS). The experimental day was divided into six shifts: morning (6:00 to 9:55 a.m.), intermediate (10:00 a.m. to 1:55 p.m.), afternoon (2:00 to 5:55 p.m.), evening (6:00 to 9:55 p.m.), night (10:00 p.m. to 1:55 a.m.), and early morning (2:00 to 5:55 a.m.). The WS group was kept in silvipastoral system paddocks, while the WOS group was kept in unshaded paddocks. Climatic data were registered and temperature and humidity index (THI) were calculated. Behavior data such as grazing, rumination, idle time, and other activities (walking, defecating, mounting, drinking water, urinating, eating salt) were evaluated. The results showed that the THI was higher in the WOS group. Grazing time was higher in the WOS group than in the WS group in the intermediate shift (p < 0.05), while in the afternoon, evening, and early morning shifts, the WS group spent more time grazing than the WOS group. In the intermediate and early morning shifts, the WS group spent more time ruminating (p < 0.05); the WS group ruminated more than the WOS group. The WOS group had more idle time, especially in the evening and early morning shifts (p < 0.05), while the WS group had more idle time in the intermediate shift (p < 0.05). We conclude that buffaloes graze and ruminate more intensely when they are reared in a shaded system on the island of Marajó.